The Greeks - Kitto, Humphrey Davy Findley (Taylor and Francis, 2007)
Cover Page -- Title Page -- Copyright Page -- Contents -- 1 Introduction -- 2 The Formation of the Greek People -- 3 The Country -- 4 Homer -- 5 The Polis -- 6 Classical Greece: The Early Period -- 7 Classical Greece: The Fifth Century -- 8 The Greeks at War -- 9 The Decline of the Polis -- 10 The Greek Mind -- 11 Myth and Religion -- 12 Life and Character -- Index.